Oxytocin Relieves Neuropathic Pain Through GABA Release and Presynaptic TRPV1 Inhibition in Spinal Cord - Sun, Wuping; Zhou, Qian; Ba, Xiyuan; Feng, Xiaojin; Hu, Xuexue; Cheng, Xiaoe; Liu, Tao; Guo, Jing; Xiao, Lizu; Jiang, Jin; Xiong, Donglin; Hao, Yue; et al. (Frontiers in Molecular Neuroscience, 2018)
Objective: Oxytocin (OT) is synthesized within the paraventricular nucleus and supraoptic nucleus of the hypothalamus. In addition to its role in uterine contraction, OT plays an important antinociceptive role; however, the underlying molecular mechanisms of antinociceptive role of OT remain elusive. We hypothesized that the antinociceptive effect of OT on neuropathic pain may occur via inhibition of TRPV1 activation in the spinal cord. The present study explores the antinociceptive role of OT and its mechanisms in neuropathic pain. Methods: Partial sciatic nerve ligation (pSNL) was performed to induce neuropathic pain. Animal behaviors were measured using a set of electronic von Frey apparatus and hot plate. Electrophysiological recordings and molecular biological experiments were performed. Results: Intrathecal administration of OT alleviated both mechanical allodynia and thermal hyperalgesia in pSNL rats (n = 6, per group, P < 0.0001, saline vs. OT group). Electrophysiological data revealed that OT significantly inhibited the enhancement of frequency and amplitude of spontaneous excitatory post-synaptic currents induced presynaptically by TRPV1 activation in the spinal cord. Moreover, the inhibitory effect of OT on capsaicin-induced facilitation of excitatory transmission was blocked by co-treatment with saclofen, while intrathecal administration of OT dramatically inhibited capsaicin-induced ongoing pain in rats, (n = 6, per group, P < 0.0001, saline vs. OT group). The paw withdrawal latency in response to heat stimulation was significantly impaired in TRPV1KO mice 3 days after pSNL upon OT (i.t.) treatment, compared with wild type mice (n = 6, P < 0.05). Finally, OT prevented TRPV1 up-regulation in spinal cords of pSNL model rats. Conclusion: OT relieves neuropathic pain through GABA release and presynaptic TRPV1 inhibition in the spinal cord. OT and its receptor system might be an intriguing target for the treatment and prevention of neuropathic pain.